Pengaruh Jaminan, Empati Dan Kehandalan Terhadap Kepuasan Pelanggan Pada KPR Bank BJB Cabang Bogor - Setiawan, Budi; ., Ferawati (LPPM Institut Bisnis dan Informatika Kesatuan, 2018)
This research is purposed to obtain and analyze the description of assurance, empathy and reliability implemented by the employees of KPR Bank BJB Bogor and how they partially and simultaneously affecting the customers satisfaction. This study is based on the assosiative analysis technique, where the populations are the customers of KPR Bank BJB Bogor office. The Slovin technique is used to obtain 10% sample size error of 99.33 or 100 people. To further analyze the data, descriptive and multiple linear analyses are applied.The survey result revealed that the assurance, empathy and reliability have all been implemented by the service person. Assurance, empathy, and reliability are proved to have influence on the customers’ satisfaction and are also have significant effect both partially and simultaneously on customers’ satisfaction.